2023
DOI: 10.1519/jsc.0000000000004095
|View full text |Cite
|
Sign up to set email alerts
|

Acute Citrulline-Malate Supplementation Increases Total Work in Short Lower-Body Isokinetic Tasks for Recreationally Active Females During Menstruation

Abstract: Gills, JL, Spliker, B, Glenn, JM, Szymanski, D, Romer, B, Lu, H-C, and Gray, M. Acute citrulline-malate supplementation increases total work in short lower-body isokinetic tasks for recreationally active females during menstruation. J Strength Cond Res 37(6): 1225-1230, 2023-Citrulline-malate (CM) exhibits acute ergogenic benefits through nitric oxide production (NO) and augmentation of vasodilatory properties. Nitric oxide is upregulated by estrogen and may influence CM's ergogenic efficacy in women. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…An acute 8 g dose of CitMal has been shown to enhance maximal hand grip strength as well as peak power output during a 30 s Wingate test in a sample of female Masters tennis athletes [ 61 ]. Gills et al [ 62 ] demonstrated that an acute 8 g dose of CitMal significantly increased work performed during a bout of five maximal isokinetic leg extensions, but provided no ergogenic benefit during 50 repetitions of maximal isokinetic leg extensions in recreationally trained women. Most other studies showing favorable effects have evaluated the effect of CitMal supplementation on muscle endurance during high-intensity resistance training as indicated by repetitions to failure.…”
Section: Effect Of L-citrulline Supplementation On Strength Performancementioning
confidence: 99%
“…An acute 8 g dose of CitMal has been shown to enhance maximal hand grip strength as well as peak power output during a 30 s Wingate test in a sample of female Masters tennis athletes [ 61 ]. Gills et al [ 62 ] demonstrated that an acute 8 g dose of CitMal significantly increased work performed during a bout of five maximal isokinetic leg extensions, but provided no ergogenic benefit during 50 repetitions of maximal isokinetic leg extensions in recreationally trained women. Most other studies showing favorable effects have evaluated the effect of CitMal supplementation on muscle endurance during high-intensity resistance training as indicated by repetitions to failure.…”
Section: Effect Of L-citrulline Supplementation On Strength Performancementioning
confidence: 99%
“…Citrulline malate is typically provided as an acute 8 g (g) dose in a 1:1 or 2:1 ratio which would yield approximately 4.0 to 5.3 g of L-citrulline and 3.7 to 4.0 g of malate. Some studies have shown that 8 g of citrulline malate could delay fatigue, improve power output, and increase the work performed during resistance exercise [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, others have failed to demonstrate an ergogenic benefit following 8 g of citrulline malate [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%